Plasmonic nanostructures for light trapping in thin-film solar cells. (15th March 2019) - Morawiec, S.; Mendes, M.J.; Priolo, F.; Crupi, I.
Abstract: The optical properties of localized surface plasmon resonances (LSPR) sustained by self-assembled silver nanoparticles are of great interest for enhancing light trapping in thin film photovoltaics. First, we report on a systematic investigation of the structural and the optical properties of silver nanostructures fabricated by a solid-state dewetting process on various substrates. Our study allows to identify fabrication conditions in which circular, uniformly spaced nanoparticles are obtainable. The optimized NPs are then integrated into plasmonic back reflector (PBR) structures. Second, we demonstrate a novel procedure, involving a combination of opto-electronic spectroscopic techniques, allowing for the quantification of useful and parasitic absorption in thin photovoltaic absorber deposited on top of the PBR. We achieve a significant broadband useful absorption enhancement of 90% for 0.9 µm thick μc-Si:H film and demonstrate that optical losses due to plasmonic scattering are insignificant below 730 nm. Finally, we present a successful implementation of a plasmonic light trapping scheme in a thin film a-Si:H solar cell. The quantum efficiency spectra of the devices show a pronounced broadband enhancement resulting in remarkably high short circuit current densities ( J sc ).